Impact of Solubility Enhancement Methods on the Dissolution Rate of Valsartan Sachet - Anjam H. Abdalla; Anoosh B. Hagop; Dina A. Boya (Polytechnic Journal)
The oral drug delivery is the most generally used route of administration that has been explored for the delivery of drugs through various pharmaceutical products. Solubility of drug plays critical role in achieving the optimum therapeutic levels of the drug in blood and thus bioavailability. There are many drugs of various therapeutic categories fall in Biopharmaceutics Classification System Classes II and IV as they lack solubility. For all these drugs, dissolution is the big issue for the absorption process. Valsartan is an effective antihypertensive agent and it can be used for the treatment of hypertension in most cases. The objective of this study is to prepare Valsartan as an oral sachet which can be used as an alternative dosage form after improvement of drug solubility using solubilizing agents such as sodium lauryl sulfate and tween 80. Three different formulas of Valsartan sachet were prepared by conventional technique of wet granulation method named conventional formula (Fc), sodium lauryl sulfate formula (Fs), and tween 80 formula (Ft) then compared with the available marketed product of Valsartan tablet (Fd) as a reference. The preformulations studies were conducted to exclude drug excipients interaction. Evaluation was performed in terms of weight variation, dose content uniformity, and drug release study using dissolution test apparatus. Fourier Transforms Infrared Spectroscopy reveals no drug excipient interaction and the drug release profile for Fs and Ft formulas within 30 min was 100.16% and 104.16%, respectively, while for Fc only 57.55% of the drug was released. This difference in the release profile was statistically significant (P < 0.05) between Fs and Ft with Fc, but a non- significant difference (P > 0.05) was observed between Fs and Ft with the marketed Valsartan tablet (Fd). The results support the possibility of using the prepared formulas Fs and Ft as a Valsartan sachet for the oral administration alternative to conventional Valsartan tablets Fd